2009
DOI: 10.1021/jp9015432
|View full text |Cite
|
Sign up to set email alerts
|

Cerium Oxyhydroxide Clusters: Formation, Structure, and Reactivity

Abstract: Cerium oxyhydroxide cluster anions were produced by irradiating ceric oxide particles by using 355 nm laser pulses that were synchronized with pulses of nitrogen gas admitted to the irradiation chamber. The gas pulse stabilized the nascent clusters that are largely anhydrous [Ce(x)O(y)] ions and neutrals. These initially formed species react with water, principally forming oxohydroxy species that are described by the general formula [Ce(x)O(y)(OH)(z)](-) for which all the Ce atoms are in the IV oxidation state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
45
1
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 116 publications
5
45
1
1
Order By: Relevance
“…Regardless of the CC and TiO 2 BB numbers, the cluster anions never accommodated more than 3 H 2 O moieties. These results are not consistent when comparing them with a previous study concerning cerium oxy-hydroxide anions [25]. Aubriet et al showed that the number of H 2 O moieties increases with the cluster anion size, i.e., the number of CeO 2 BB.…”
Section: Resultscontrasting
confidence: 79%
See 4 more Smart Citations
“…Regardless of the CC and TiO 2 BB numbers, the cluster anions never accommodated more than 3 H 2 O moieties. These results are not consistent when comparing them with a previous study concerning cerium oxy-hydroxide anions [25]. Aubriet et al showed that the number of H 2 O moieties increases with the cluster anion size, i.e., the number of CeO 2 BB.…”
Section: Resultscontrasting
confidence: 79%
“…This was more specifically supported by the results reported in the literature discussing the investigation of alumina [26][27], silica [29], chromia [35,36], or ceria [25] oxyanions and oxy-hydroxide anions. A portion of the oxy-hydroxide cluster anions was obtained by the ion-molecule reaction in the gas phase between metal oxide ions and water molecules, which involves the (1) incorporation of "water" in the cluster ion, and (2) formation of hydroxyl groups.…”
Section: Tandem Mass Spectrometry Measurementssupporting
confidence: 74%
See 3 more Smart Citations